Ordinal scoring of coronary artery calcification in low dose computed tomography is predictive factor of all-cause death and cardiovascular events. (3rd October 2022) - Kasprzyk, P; Undrunas, A; Dziedzic, R; Szurowska, E; Gruchala, M; Gierlotka, M; Jaguszewski, M; Rzyman, W; Zdrojewski, T
Abstract: Background: Lung cancer and cardiovascular disease (CVD) are leading worldwide mortality causes firmly related to smoking. Lung cancer screening (LCS) consisted in performing low-dose computed tomography (LDCT) offers an opportunity for simultaneous coronary artery calcification (CAC) assessment. Purpose: The study aimed to determine the usefulness of the visual assessment of CAC in the prediction of all-cause death and non-fatal cardiovascular outcomes including myocardial infarction and stroke. Methods: The study involved 6580 participants aged 50–79 years, current or former smokers with a cigarette smoking history of at least 30 pack-years, who were qualified for lung cancer screening program performed between April 2016 and May 2018. CAC was visually scored on ungated LDCT scans in the range of 0–12 based on the length of calcification involvement in four main coronary arteries. CAC severity was categorized into groups of 0, 1–3, 4–12. The primary outcome was all-cause mortality. The secondary outcome was major adverse cardiovascular events (composite of CVD death, nonfatal myocardiaI infarction, nonfatal stroke). The outcomes data were obtained by using the National Health Care Provider Registry of death and hospitalizations. The mean time of follow-up was 41.1 months (SD 8.3). Logistic regression analysis was used to determine the risk of mortality according to the CAC category adjusted for age, pack-years of cigarette smoking, and sex. Results: The rate of all-cause death substantially increased in groups of higher CAC and it was consecutively 2.7% (89 of 3288 subjects) for a score of 0, 4.2% (66 of 1582 subjects) for a score of 1–3 and 8.3% (145 of 1742 subjects) for a score of 4–12. With the use of subjects with a CAC score of 0 as the reference group, adjusted for sex, age, and pack-years of smoking, a CAC score of at least 4 was a significant predictor of all-cause death (hazard ratio [HR], 1.89; 95% CI: 1.42; 2.52; P<0.05). Similar results were observed for the composite of CVD death, nonfatal myocardial infarction, nonfatal stroke with even greater significance. The rate of secondary outcames was 1.6% (51/3276) in a 0 score cohort, 3.0% (47/1570) in a 1–3 score cohort and 7.5% (130/1732) in a 4–12 score cohort. Both CAC score in the range 1–3 ([HR], 1.57; 95% CI: 1.05; 1.2.35; P<0.05), and 4–12 ([HR], 3.55; 95% CI: 2.50; 5.04; P<0.05) were a significant predictors of major adverse cardiovascular event incidence. Conclusions: Visual assessment of CAC provides solid evidence of all-cause death and cardiovascular incidents independently of traditional coronary risk factors. Therefore evaluation of CAC in LDCT scans offers a unique opportunity for instituting CVD risk assessment in lung cancer screening program. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Centre for Research and Development of Poland.